Visual Mismatch Negativity Reflects Enhanced Response to the Deviant: Evidence From Event-Related Potentials and Electroencephalogram Time-Frequency Analysis - Zeng, Xianqing; Ji, Luyan; Liu, Yanxiu; Zhang, Yue; Fu, Shimin (Frontiers in Human Neuroscience, 2022)
Automatic detection of information changes in the visual environment is crucial for individual survival. Researchers use the oddball paradigm to study the brain’s response to frequently presented (standard) stimuli and occasionally presented (deviant) stimuli. The difference wave is called visual mismatch negativity (vMMN), which is obtained by subtracting event-related potentials (ERPs) evoked by the deviant from ERPs evoked by the standard. There are three hypotheses to explain the vMMN. The sensory fatigue (or refractoriness) hypothesis considers that weakened neural activity caused by repetition results in decreased ERPs of the standard. The memory trace hypothesis proposes that vMMN results from increased responses to the deviant. The predictive coding hypothesis attributes changes to a combination of the two effects. However, when distinguishing between these effects, previous researchers did not consider the effect of low-level features on the vMMN. In this experiment, we presented an oddball sequence, reverse oddball sequence, and equiprobable sequence. The standard (fear face, presented at 80% probability) of the reverse oddball sequence and the same type of stimulus (fear face, 20%) of the equiprobable sequence were subtracted from the deviant (fear face, 20%) of the oddball sequence. The influence of the presentation probability of the standard on the vMMN (i.e., refractoriness) was tested, excluding the effect of low-level features. The results showed no significant difference between the reverse oddball vMMN and the equiprobable vMMN within the range of 100 to 350 ms following stimulus onset, while the vMMN effect was significant, indicating the probability of the standard did not affect vMMN, which supported the memory trace hypothesis. Additionally, the fear face induced more negative vMMN than the neutral within the range of 100 to 150 ms, suggesting a negative bias. Time-frequency analysis showed that the deviant had stronger oscillatory responses in theta band than the standard (vMORs). However, there was no difference between reverse oddball vMORs and equiprobable vMORs, indicating that vMORs reflect an enhanced response to the deviant in terms of neural oscillation, which supports the memory trace hypothesis.